Teaching English as Third Language to Tribal Students : Evolving Teaching Techniques and Reading Testing Material - Sindkhedkar, Sushil Kumar (THE PRIMARY TEACHER, 2008)
The UGC, under its IX and X plans, has been liberally sanctioning Special Remedial English Coaching Grants for the SC/ST students enrolled in colleges affiliated to and conducted by different universities all over the country. The State of Maharashtra has accepted the National Education Policy, and therefore it has implemented the ‘Three Language Formula’ in the primary, secondary and higher secondary schools as well as in colleges. The ‘Three Language Formula’ expects the student to learn his/her mother tongue Marathi as L1, Hindi as well as English as L2. Though the State has faithfully implemented the ‘Three Language Formula’, it seems that the same policy does not work properly in the case of tribal students. The tribal students speak their mother tongue ‘Bhillori’ and it is L1 for them. The regional language of Maharashtra i.e. ‘Marathi’ is L2 to the tribal students and English is L3. The school as well as college syllabus of English has been framed by accepting the ‘Three Language Formula’ and English as L2 for all the students of Maharashtra. The syllabus of English has been framed by accepting the fact that English is L2. However, for tribal students, English is L3 and therefore, the syllabus of English for them needs several modifications or perhaps a new English syllabus should be designed for English as L3. After conducting surveys (one for the tribal students and second for their English teachers) the Paper has enough data to substantiate the difficulties that the tribal students have been facing while learning English as L2 and reading English texts prepared for students for whom English is L2. The paper has suggested that the English texts for the school and college tribal students should be reprepared by accepting the fact that for them English is L3 and not L2. It is now evident that along with the new texts the teaching and testing material should also be redesigned.